2015
DOI: 10.3803/enm.2015.30.4.543
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recurrence in Filipinos with Well-Differentiated Thyroid Cancer

Abstract: BackgroundThe incidence of well-differentiated thyroid cancer (WDTC) has increased in recent years. Despite its excellent prognosis, increasing morbidity from recurrent diseases continues to affect long-term outcomes. Among at-risk populations, Filipinos have the highest incidence of thyroid cancer worldwide, characterized by a highly aggressive and recurrent form of disease. Here, we sought to identify risk factors associated with disease recurrence among Filipinos with WDTC.MethodsThis retrospective cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Recent studies have demonstrated that tumor size, nodal metastases, and histological type are often associated to postoperative recurrence of TC [30, 45, 46]. In addition to this, Gandolfi et al revealed that mutations in the hTERT promoter are closely associated to metastasis in papillary TC [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that tumor size, nodal metastases, and histological type are often associated to postoperative recurrence of TC [30, 45, 46]. In addition to this, Gandolfi et al revealed that mutations in the hTERT promoter are closely associated to metastasis in papillary TC [47].…”
Section: Discussionmentioning
confidence: 99%
“…Our results also revealed that postoperative recurrence of TC was associated to pathologic types and tumor stages and that the DNA methylation levels and the rs2736100 polymorphisms of hTERT gene were associated to the tumor size, multicentricity, extrathyroidal invasion, pathologic types, lymph node metastases, and tumor stage of the recurrence group. Recent studies have demonstrated that tumor size, nodal metastases, and histological type are often associated to postoperative recurrence of TC [ 30 , 45 , 46 ]. In addition to this, Gandolfi et al revealed that mutations in the hTERT promoter are closely associated to metastasis in papillary TC [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors analyzed the clinical features and recurrence rate compared to other Asian populations, including Koreans. These same authors previously reported risk factors for DTC recurrence in Filipinos at Philippine General Hospital [ 14 ].…”
mentioning
confidence: 89%
“…In Filipino American women, a higher rate of recurrence was reported, especially in premenopausal women. The long-term survival rate was also lower in those females compared to any other ethnic group [ 7 , 8 , 12 , 13 , 14 , 15 , 16 ]. Recently, it has been found that the recurrence rate is also higher in Filipino Americans [ 7 , 10 , 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The long-term survival rate was also lower in those females compared to any other ethnic group [ 7 , 8 , 12 , 13 , 14 , 15 , 16 ]. Recently, it has been found that the recurrence rate is also higher in Filipino Americans [ 7 , 10 , 12 , 15 , 16 ]. Therefore, identifying biomarkers for the prognosis of PTC in Filipino Americans is one of the most important issues in TC health disparities for monitoring cancer progression.…”
Section: Introductionmentioning
confidence: 99%